Anti-inflammatory, antipyretic efficacy and safety of inhaled Houttuynia cordata thunb. essential oil formulation. (28th October 2022) - Wong, Chun Fai; Poon, Cheuk Ka; Ng, Tsz Wai; Pan, Hok Him; Khaw, Eng Cheng; Tsang, Ki Fong; Mui, Yan Wing; Lo, Yuk Hong; Hao, Mui Fung; Ko, Chun Hay
Abstract: Ethnopharmacological relevance: Houttuynia cordata Thunb. ( H. cordata ) is a well-known folk traditional Chinese medicine that is renowned for its use in the management of inflammatory respiratory diseases and pneumonia. Its essential oils have demonstrated their anti-inflammatory efficacy in vitro, however, their in vivo biological effects via inhalation have not been elucidated. Aim of the study: This study aims to evaluate the anti-inflammation and toxicology of H. cordata essential oil-containing formulation, H16 aerosol in vivo . Materials and methods: A laser diffraction particle size analyser and a Next Generation Impactor were used to measure the mass median aerodynamic diameter (MMAD) of the H16 aerosol. The anti-inflammatory and antipyretic effects of the H16 aerosol were evaluated in the xylene-evoked ear oedema and Brewer's yeast-induced fever models, respectively. The biological safety of the H16 aerosol was evaluated by acute toxicity and local toxicity tests in animal models. Results: Our data showed that the MMAD of the bioactive aerosol was 3–5 μm, which implied tracheal and pharyngeal deposits. Significant anti-inflammatory and antipyretic effects were also observed in the animal models treated with H16 aerosol. The maximum tolerable dose of H16 in rats was >2.5 mL/kg. Irritation was not found on respiratory tract mucosa in the local toxicity test. Conclusions: Taken together, the present study suggested that H16 could be delivered in the form of aerosol and possessed its antipyretic and anti-inflammatory effects. This study provides a new perspective for the development of a new herbal aerosol therapy and herbal modernization. Graphical abstract: Image 1